Preparation method of CuO / Cu2O modified graphene flexible sweat glucose sensor

The preparation method of flexible sweat glucose sensors that modify and reduce graphene oxide by CuO/Cu2O, combined with microelectronic flexible printing technology, solves the problem of insufficient sensitivity and stability of traditional enzyme-containing biosensors, and achieves efficient, sensitive, selective and low-cost glucose detection effects.

CN116421177BActive Publication Date: 2025-04-04HARBIN UNIV OF SCI & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310406870.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-17
Publication Date
2025-04-04
Estimated Expiration
2043-04-17

AI Technical Summary

Technical Problem

The existing traditional enzyme-containing biosensors are affected by environmental factors such as temperature and pH, resulting in insufficient sensitivity and stability.

Method used

The preparation method of flexible sweat glucose sensor using CuO/Cu2O modified and reduced graphene oxide was designed by combining CuO/Cu2O/RGO composite materials with microelectronic flexible printing technology.

Benefits of technology

A glucose sensor with excellent operating performance under extremely small volume and extremely low power consumption is achieved, with high sensitivity, stability and selectivity, and can quickly and accurately detect glucose in sweat.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116421177B_ABST
    Figure CN116421177B_ABST
Patent Text Reader

Abstract

A method for preparing a CuO / Cu2O modified graphene flexible sweat glucose sensor, the invention belongs to the field of wearable electrochemical sensors. The invention is to solve the technical problem that the activity of bioactive substances such as enzymes will be affected by environmental factors such as temperature and pH, resulting in insufficient sensitivity and stability of the existing traditional enzyme-containing biosensors. Methods: 1. Preparation of CuO / Cu2O modified materials; 2. Preparation of reduced graphene oxide; 3. Preparation of electrochemical electrodes; 4. Preparation of microheaters; 5. Cu x Coating of O / RGO composite material; Sixth, assembly of sensor. The present invention prepares the synthetic Cu x The O / RGO composite material uses Cu as a working electrode, which has the advantages of good contact between the electrode active material and the conductive Cu substrate and low cost. The sensor prepared by the present invention is used to detect glucose.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of wearable electrochemical sensors, and in particular relates to a method for preparing a CuO / Cu2O modified graphene flexible sweat glucose sensor. Background Art

[0002] Recently, relevant scientific research has confirmed an important discovery through data: diabetes is the main risk factor for developing severe pneumonia and sepsis caused by viral infection, and about 20% of pneumonia patients also have diabetes. At present, diabetes has become the third largest disease threatening human health after cancer and cardiovascular disease.

[0003] The content of electrolytes, lactic acid, glucose and other chemical substances in sweat reflects the health of the human body. Glucose is the main component of blood sugar in the human body and provides the main energy source for human activities. That is, under normal circumstances, the glucose in the human body needs to be maintained within a certain concentration range. Hypoglycemia or hyperglycemia will have a direct harm to human health. Relatively speaking, the harm caused by hyperglycemia to human health is more serious, such as obesity, diabetes and other diseases. The development of low-cost, highly sensitive and selective glucose sensors is of great significance for the prevention and treatment of diabetes.

[0004] Traditional blood glucose meters are all invasive blood sampling tests, which bring pain and infection risks to patients. The development of non-invasive sweat glucose monitoring sensors has also been a hot research topic in recent years. Compared with the detection of blood sugar, skin interstitial fluid and other detection targets, monitoring blood sugar by detecting glucose in human sweat has more significant advantages. This detection method can achieve the purpose of non-invasive continuous monitoring. The highly sensitive system that can monitor glucose in sweat has important research value.

[0005] In recent years, breakthroughs in wearable auxiliary sensor technology have further promoted the development of electrochemical sensors in rapid on-site detection. Wearable analysis devices based on electrochemical principles have the advantages of portability, high sensitivity and continuous monitoring, and have great potential in the detection of biochemical indicators in body fluids. Therefore, the preparation of a wearable enzyme-free glucose sweat detection system based on the principle of electrochemical analysis has become a hot topic and difficulty in current research.

[0006] As a new type of two-dimensional carbon nanomaterial, graphene has a large specific surface area, good conductivity, and remarkable mechanical and thermal stability. It is a very promising electrode material in non-enzyme glucose sensors. The electrochemical properties of graphene are also outstanding. For example, its ultra-high specific surface area and conductivity can effectively promote its binding with the molecules to be tested, thereby improving the detection sensitivity and greatly reducing the detection limit.

[0007] Therefore, the use of electrodes modified with metal and its oxide and graphene composite materials, supplemented by temperature compensation module structure process design, is expected to solve a series of problems caused by the defects of traditional enzyme-based sensors, further expand the research field of sweat glucose sensors and achieve results. Summary of the invention

[0008] The present invention aims to solve the technical problem that the activity of bioactive substances such as enzymes will be affected by environmental factors such as temperature and pH, resulting in insufficient sensitivity and stability of the existing traditional enzyme-containing biosensors, and provides a method for preparing a flexible sweat glucose sensor of CuO / Cu2O modified reduced graphene oxide.

[0009] A method for preparing a CuO / Cu2O modified graphene flexible sweat glucose sensor is specifically carried out according to the following steps:

[0010] 1. Preparation of CuO / Cu2O modified materials

[0011] a. Mix copper chloride CuCl2 powder with deionized water to prepare CuCl2 solution;

[0012] Mix sodium hydroxide NaOH powder with deionized water to prepare a NaOH solution;

[0013] Add the NaOH solution to the CuCl2 solution while stirring, control the pH value of the solution to 7, and react fully to obtain a blue suspension of copper hydroxide Cu(OH)2;

[0014] b. Centrifuge the obtained copper hydroxide Cu(OH)2 blue suspension in a low-speed centrifuge, wash with deionized water, repeat the centrifugation and washing process 3-4 times, wash once with anhydrous ethanol, remove the supernatant, and obtain a Cu(OH)2 blue colloidal precipitate;

[0015] c. Place the obtained Cu(OH)2 blue colloidal precipitate in a quartz boat, control the temperature at 70-90°C to dry for 2 hours, then grind it into powder, transfer it to a vacuum drying oven, control the temperature at 200-250°C to roast for 3 hours, and use a ball mill to fully grind it to obtain fine black copper oxide CuO powder;

[0016] d. Mix copper sulfate CuSO4 and sodium hydroxide NaOH, react at room temperature to generate blue copper hydroxide Cu(OH)2 suspension, heat in a water bath to 70°C, add glucose solution, then add NaOH solution to react until the solution turns reddish brown, then keep the temperature constant for 50-70 minutes and stop heating;

[0017] e. Filter the solution obtained in step d, rinse, dry, and then grind to obtain a dense reddish-brown Cu2O powder;

[0018] 2. Preparation of reduced graphene oxide RGO

[0019] f. Ultrasonic dispersion of the graphene solution to obtain a graphene dispersion, which is then dried in a cool place to obtain graphene oxide, and then the graphene oxide is placed in an agate mortar for full grinding to obtain reddish-brown graphene oxide powder;

[0020] g. dissolving the prepared red-brown graphene oxide powder in deionized water and dispersing by ultrasonication to obtain a red-brown uniform graphene oxide solution;

[0021] h. The obtained reddish-brown uniform graphene oxide solution is transferred to a high-pressure reactor, and the temperature is controlled at 130-135° C. in a vacuum drying oven to perform a reduction reaction;

[0022] i. The product obtained by the reduction reaction is repeatedly washed with deionized water for several times, and then repeatedly washed with anhydrous ethanol for several times; then filtered, impurities are removed, dried, and fully ground to obtain fine reduced graphene oxide powder, which is recorded as RGO;

[0023] 3. Preparation of electrochemical electrodes

[0024] j. Electrochemical electrodes were prepared on PET film using a microelectronic flexible printing device based on a digital three-dimensional model;

[0025] 4. Preparation of Microheater

[0026] k. The micro heater is a heating device with a controlled temperature range of 32 to 40°C; the heating device is a micro heater module with a temperature compensation function, so that it can achieve the purpose of simulating human body temperature. The temperature compensation heating unit is placed at the bottom of the sensor to achieve temperature compensation of human sweat detection parameters;

[0027] 5. Cu x Coating of O / RGO composites

[0028] 1. The CuO powder prepared in step c, the Cu2O powder prepared in step e and the RGO prepared in step i are placed in an agate mortar, pinene alcohol is added, and the mixture is fully ground to obtain a CuO / Cu2O / RGO slurry raw material. The CuO / Cu2O / RGO slurry raw material is coated on the effective contact area of ​​the working electrode in the electrochemical electrode prepared in step j, dried at room temperature, and then transferred to a vacuum drying oven and vacuum dried at 200-220° C. for 2-2.5 hours; Nafion perfluorinated solution is then coated on the surface of the working electrode, air-dried to form a film, and a CuO / Cu2O modified reduced graphene oxide electrode is obtained;

[0029] 6. Sensor Assembly

[0030] m. Assemble the flexible substrate, the microheater obtained in step k, the isolation layer and the CuO / Cu2O modified reduced graphene oxide electrode obtained in step l from bottom to top to complete the preparation method of the CuO / Cu2O modified graphene flexible sweat glucose sensor.

[0031] Preparation of the isolation layer:

[0032] 10g of white solid particles of polyvinyl alcohol and 5mL of anhydrous ethanol are dissolved in 100mL of aqueous solution, and heated in a water bath at 80°C. A magnetic stirrer is used at a speed of 100-500r / min to allow it to react fully. The water bath heating time is 3-5h. After the stirring and heating, a viscous liquid is formed as an isolation membrane source material. The viscous liquid is then placed in a microelectronic flexible printer and coated with a dispensing process to form a thin film with a thickness of 0.2-0.4mm. The film is allowed to stand for 24h and then transferred to an oven, dried at 80°C for 5-6h, to finally form a solidified isolation membrane.

[0033] The method for detecting sweat glucose by the sensor is as follows:

[0034] The sensor is connected to an electrochemical workstation, and the liquid to be tested is dropped into the effective contact area of ​​the working electrode of the sensor. The temperature of the micro heater is controlled to be 32-40° C. for detection and analysis.

[0035] Beneficial effects of the present invention:

[0036] The present invention breaks through the shortcomings of enzyme-based glucose sensors that are constrained by the instability of the enzyme itself, and are prone to inactivation, degradation and consumption under certain conditions, which puts the sensitivity and stability of the detection results under great test. The CuO / Cu2O / RGO composite material is prepared and synthesized, and Cu is used as the working electrode. It has the advantages of good contact between the electrode active material and the conductive Cu substrate and low cost. At the same time, the electrochemical electrode is printed on the flexible substrate material using microelectronic flexible printing technology so that it can fit closely with the skin surface. At the same time, it is supplemented by a newly designed microheater structure, so that it exhibits excellent working performance during the detection process, thereby designing an efficient, sensitive, selective, low-cost and highly stable enzyme-free glucose detection system.

[0037] Among various transition metal oxides, copper oxide is favored by researchers due to its advantages of non-toxicity, low cost, green environmental protection and easy preparation. Since CuO and Cu2O are oxides of the same element with different valence states, the present invention uses the advantage that the asymmetric structure produced by the combination of the two is more conducive to the improvement of catalytic performance to prepare the composite material; and graphene, as a new type of carbon nanomaterial, was found in early studies that its modified electrode composited with copper has better electrocatalytic performance for the oxidation and detection of glucose. Therefore, it is crucial and promising to conduct more in-depth research in the research field related to copper and its metal oxides combined with modified materials such as graphene.

[0038] The CuO / Cu2O modified reduced graphene oxide flexible sweat glucose sensor prepared by the present invention can also have excellent working performance under extremely small volume and extremely low power consumption conditions. With the prepared sensitive modified material, the sensor chip has the advantages of high production automation, rapid and accurate response to glucose detection, and stable working performance for a long time. In the process of catalytic oxidation of glucose, the composite of metallic copper and its oxide and reduced graphene oxide plays a great role, thereby showing very excellent glucose sensitivity.

[0039] The present invention adopts flexible substrate materials and combines microelectronic flexible printing technology, so that the prepared electrochemical sensor can fit tightly with the skin, and is assisted by the development of a micro heater to simulate human body temperature and achieve the best suitable detection temperature, ensuring that when sweat samples are extracted, the measurement effect is not affected by climate change due to human body temperature, which will cause errors, thereby greatly improving detection efficiency and accuracy.

[0040] The sensor prepared by the invention is used for detecting glucose. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 This is a SEM image of CuO powder prepared in step 1 of Example 1;

[0042] Figure 2 This is a SEM image of Cu2O powder prepared in step 1 of Example 1;

[0043] Figure 3 This is the SEM image of RGO prepared in step 2 of Example 1;

[0044] Figure 4 This is a SEM image of the CuO / Cu2O / RGO slurry material prepared in step 5 of Example 1;

[0045] Figure 5 This is a schematic diagram of the structure of the electrochemical electrode prepared in step 3 of Example 1;

[0046] Figure 6This is a schematic diagram of the structure of preparing a micro-heater in step 4 of Example 1;

[0047] Figure 7 This is a schematic diagram of the structure of the sensor prepared in Example 1; the heating layer is a microheater, and the electrode layer is an electrochemical electrode;

[0048] Figure 8 This is a schematic diagram of preparing a sensor for detection in Example 1;

[0049] Fig. 9 This is a data analysis diagram of the sensor prepared in Example 1 using cyclic voltammetry to detect different concentrations of glucose. DETAILED DESCRIPTION

[0050] Specific implementation method 1: This implementation method is a method for preparing a CuO / Cu2O modified graphene flexible sweat glucose sensor, which is specifically carried out in the following steps:

[0051] 1. Preparation of CuO / Cu2O modified materials

[0052] a. Mix copper chloride CuCl2 powder with deionized water to prepare CuCl2 solution;

[0053] Mix sodium hydroxide NaOH powder with deionized water to prepare a NaOH solution;

[0054] Add the NaOH solution to the CuCl2 solution while stirring, control the pH value of the solution to 7, and react fully to obtain a blue suspension of copper hydroxide Cu(OH)2;

[0055] b. Centrifuge the obtained copper hydroxide Cu(OH)2 blue suspension in a low-speed centrifuge, wash with deionized water, repeat the centrifugation and washing process 3-4 times, wash once with anhydrous ethanol, remove the supernatant, and obtain a Cu(OH)2 blue colloidal precipitate;

[0056] c. Place the obtained Cu(OH)2 blue colloidal precipitate in a quartz boat, control the temperature at 70-90°C to dry for 2 hours, then grind it into powder, transfer it to a vacuum drying oven, control the temperature at 200-250°C to roast for 3 hours, and use a ball mill to fully grind it to obtain fine black copper oxide CuO powder;

[0057] d. Mix copper sulfate CuSO4 and sodium hydroxide NaOH, react at room temperature to generate blue copper hydroxide Cu(OH)2 suspension, heat in a water bath to 70°C, add glucose solution, then add NaOH solution to react until the solution turns reddish brown, then keep the temperature constant for 50-70 minutes and stop heating;

[0058] e. Filter the solution obtained in step d, rinse, dry, and then grind to obtain a dense reddish-brown Cu2O powder;

[0059] 2. Preparation of reduced graphene oxide RGO

[0060] f. Ultrasonic dispersion of the graphene solution to obtain a graphene dispersion, which is then dried in a cool place to obtain graphene oxide, and then the graphene oxide is placed in an agate mortar for full grinding to obtain reddish-brown graphene oxide powder;

[0061] g. dissolving the prepared red-brown graphene oxide powder in deionized water and dispersing by ultrasonication to obtain a red-brown uniform graphene oxide solution;

[0062] h. The obtained reddish-brown uniform graphene oxide solution is transferred to a high-pressure reactor, and the temperature is controlled at 130-135° C. in a vacuum drying oven to perform a reduction reaction;

[0063] i. The product obtained by the reduction reaction is repeatedly washed with deionized water for several times, and then repeatedly washed with anhydrous ethanol for several times; then filtered, impurities are removed, dried, and fully ground to obtain fine reduced graphene oxide powder, which is recorded as RGO;

[0064] 3. Preparation of electrochemical electrodes

[0065] j. Electrochemical electrodes were prepared on PET film using a microelectronic flexible printing device based on a digital three-dimensional model;

[0066] 4. Preparation of Microheater

[0067] k. The micro heater is a heating device with a controlled temperature range of 32 to 40°C;

[0068] 5. Cu x Coating of O / RGO composites

[0069] 1. The CuO powder prepared in step c, the Cu2O powder prepared in step e and the RGO prepared in step i are placed in an agate mortar, pinene alcohol is added, and the mixture is fully ground to obtain a CuO / Cu2O / RGO slurry raw material. The CuO / Cu2O / RGO slurry raw material is coated on the effective contact area of ​​the working electrode in the electrochemical electrode prepared in step j, dried at room temperature, and then transferred to a vacuum drying oven and vacuum dried at 200-220° C. for 2-2.5 hours; Nafion perfluorinated solution is then coated on the surface of the working electrode, air-dried to form a film, and a CuO / Cu2O modified reduced graphene oxide electrode is obtained;

[0070] 6. Sensor Assembly

[0071] m. Assemble the flexible substrate, the microheater obtained in step k, the isolation layer and the CuO / Cu2O modified reduced graphene oxide electrode obtained in step l from bottom to top to complete the preparation method of the CuO / Cu2O modified graphene flexible sweat glucose sensor.

[0072] Specific implementation method 2: This implementation method is different from the specific implementation method 1 in that: in step b, the rotation speed of the low-speed centrifuge is controlled to be 3500-4000 r / min. The rest is the same as the specific implementation method 1.

[0073] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that the vacuum degree of the vacuum drying oven is controlled to be -0.1 to 0.08 MPa in step c. The rest is the same as specific implementation method 1 or 2.

[0074] Specific embodiment 4: This embodiment is different from any one of the specific embodiments 1 to 3 in that: the copper sulfate CuSO4, glucose C6H 12 The molar ratio of O6 to sodium hydroxide NaOH is 1:0.5:3. The rest is the same as that of the first to third embodiments.

[0075] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that: in step g, the ultrasonic working power is controlled to be 130-195W, and the ultrasound is turned on for 1.0s and then turned off for 1.0s, and the total time is 30min. Others are the same as specific embodiments 1 to 4.

[0076] Specific embodiment 6: This embodiment is different from specific embodiments 1 to 5 in that: the electrochemical electrodes prepared in step j are a working electrode, a counter electrode and a reference electrode; the effective contact area of ​​the working electrode is circular, the counter electrode and the reference electrode are arc-shaped structures, and the counter electrode and the reference electrode form a surrounding structure around the effective contact area of ​​the working electrode. The rest is the same as specific embodiments 1 to 5.

[0077] Specific embodiment 7: This embodiment is different from specific embodiments 1 to 6 in that the ratio of the amount of CuO, Cu2O and RGO in step 1 is 1:1:0.5. The rest is the same as specific embodiments 1 to 6.

[0078] Specific embodiment 8: This embodiment differs from specific embodiments 1 to 7 in that the mass concentration of the Nafion perfluorinated solution in step 1 is 5%. The rest is the same as specific embodiments 1 to 7.

[0079] Specific embodiment 9: This embodiment is different from any one of specific embodiments 1 to 8 in that: the isolation layer in step m is prepared as follows:

[0080] 10g of white solid particles of polyvinyl alcohol and 5mL of anhydrous ethanol are dissolved in 100mL of aqueous solution, and heated in a water bath at 80°C. A magnetic stirrer is used to fully react at a speed of 100-500r / min. The water bath heating time is 3-5h. After the stirring and heating, a viscous liquid is formed as a source material for the isolation film. The viscous liquid is then placed in a microelectronic flexible printer, and a dispensing process is used to apply it to form a film with a thickness of 0.2-0.4mm. The film is placed in an oven after standing for 24h, and then dried at 80°C for 5-6h to finally form a solidified isolation film. The rest is the same as one of the specific embodiments 1 to 8.

[0081] Specific embodiment 10: This embodiment is different from any one of specific embodiments 1 to 9 in that the method for detecting sweat glucose by the sensor is as follows:

[0082] The sensor is connected to an electrochemical workstation, the liquid to be tested is dropped into the effective contact area of ​​the working electrode of the sensor, the temperature of the micro heater is controlled to be 32-40° C., and the detection and analysis are performed. The rest is the same as the first to ninth embodiments.

[0083] The content of the present invention is not limited to the content of the above-mentioned embodiments. The combination of one or several specific embodiments can also achieve the purpose of the invention.

[0084] Embodiment 1:

[0085] The present embodiment provides a method for preparing a CuO / Cu2O modified graphene flexible sweat glucose sensor, which is specifically carried out in the following steps:

[0086] 1. Preparation of CuO / Cu2O modified materials

[0087] a. Mix copper chloride (CuCl2) powder with deionized water to prepare a CuCl2 solution with a mass concentration of 2%;

[0088] Mix sodium hydroxide NaOH powder with deionized water to prepare a NaOH solution with a mass concentration of 10%;

[0089] Use a basic burette to draw an appropriate amount of NaOH solution and slowly add it dropwise to the copper chloride CuCl2 solution, and use a magnetic stirrer to stir the resulting solution, control the pH value of the solution to 7, and react fully to obtain a blue suspension of copper hydroxide Cu(OH)2;

[0090] b. Centrifuge the obtained copper hydroxide Cu(OH)2 blue suspension in a low-speed centrifuge at a speed of 3800 r / min, wash with deionized water, repeat the centrifugation and washing process 3-4 times, wash once with anhydrous ethanol, remove the supernatant, and obtain a Cu(OH)2 blue colloidal precipitate;

[0091] c. Place the obtained Cu(OH)2 blue colloidal precipitate in a quartz boat and put it into a desktop drying oven, control the temperature to 80°C and dry it for 2 hours, then grind it into powder, transfer it to a vacuum drying oven, control the vacuum degree of the vacuum drying oven to -0.1~0.08MPa, and bake it at 230°C for 3 hours, and use a ball mill to fully grind it to obtain fine black copper oxide CuO powder;

[0092] d. Mix copper sulfate CuSO4 and sodium hydroxide NaOH, react at room temperature to generate a blue copper hydroxide Cu(OH)2 suspension, heat in a water bath to 70°C, add glucose solution, and then add a 10% NaOH solution to react until the solution turns reddish brown, keep the reaction at constant temperature for 60 minutes, and then stop heating;

[0093] The copper sulfate CuSO4, glucose C6H 12 The molar ratio of O6 and sodium hydroxide NaOH is 1:0.5:3;

[0094] e. Filter the solution obtained in step d, rinse, dry, and then grind to obtain a dense reddish-brown Cu2O powder;

[0095] 2. Preparation of reduced graphene oxide RGO

[0096] f. Ultrasonic dispersion of the graphene solution is performed using an ultrasonic cell crusher to obtain a graphene dispersion liquid, and then the graphene dispersion liquid obtained by ultrasound is poured into a glass dish, and placed in a cool place to dry to obtain graphene oxide, and then the graphene oxide is placed in an agate mortar for full grinding to obtain a reddish-brown graphene oxide powder;

[0097] g. Dissolve 0.025 g of the prepared reddish-brown graphene oxide powder in 15 mL of deionized water, and use an ultrasonic cell crusher for ultrasonic dispersion. Control the ultrasonic working power to 130 W, and turn on the ultrasound for 1.0 s and then turn off the ultrasound for 1.0 s for a total of 30 min to obtain a reddish-brown uniform graphene oxide solution.

[0098] h. The obtained reddish-brown uniform graphene oxide solution was transferred to a high-pressure reactor, and the temperature was controlled at 130° C. in a vacuum drying oven to carry out a reduction reaction for 12 hours;

[0099] i. The product obtained by the reduction reaction in step h is repeatedly washed with deionized water for multiple times, and then repeatedly washed with anhydrous ethanol for multiple times; then filtered, impurities are removed, and dried. After sufficient grinding, fine reduced graphene oxide powder is obtained, which is recorded as RGO;

[0100] 3. Preparation of electrochemical electrodes

[0101] j. Electrochemical electrodes are prepared on PET films by using a microelectronic flexible printing device based on a digital three-dimensional model. The thickness of the electrochemical electrodes is 200 nm. The PET film has a specification of 300 mm × 300 mm and a thickness of 0.125 mm. The electrochemical electrodes include a working electrode, a counter electrode and a reference electrode. The working electrode is made of Cu, the counter electrode is made of platinum, and the reference electrode is made of Ag / AgCl. The effective contact area of ​​the working electrode is circular. The counter electrode and the reference electrode are arc-shaped structures. The counter electrode and the reference electrode form a surrounding structure around the effective contact area of ​​the working electrode. One end of the reference electrode has a short arc, and there is a gap between the short arc and the effective contact area of ​​the working electrode. One end of the counter electrode extends a long arc, and there is a gap between the long arc and the effective contact area of ​​the working electrode.

[0102] 4. Preparation of Microheater

[0103] k. The micro heater is a heating device with a controlled temperature range of 32-40°C, and the specific material is a heating coil;

[0104] 5. Cu x Coating of O / RGO composites

[0105] l. Put the CuO powder prepared in step c, the Cu2O powder prepared in step e and the RGO prepared in step i in an agate mortar, wherein the ratio of the amount of CuO powder, Cu2O powder and RGO is 1:1:0.5; add pinene alcohol and grind them thoroughly to obtain a CuO / Cu2O / RGO slurry material, apply the CuO / Cu2O / RGO slurry material on the effective contact area of ​​the working electrode in the electrochemical electrode prepared in step j, dry at room temperature, and then transfer to a vacuum drying oven and vacuum dry at 200° C. for 2 h; then apply a Nafion perfluorinated solution with a mass concentration of 5% on the surface of the working electrode, and form a polymer film after the solution is air-dried to obtain a CuO / Cu2O modified reduced graphene oxide electrode;

[0106] 6. Sensor Assembly

[0107] m. Assemble the flexible substrate, the microheater obtained in step k, the isolation layer and the CuO / Cu2O modified reduced graphene oxide electrode obtained in step l from bottom to top, wherein the flexible substrate is made of PET, and the CuO / Cu2O modified reduced graphene oxide electrode is directly above the microheater, ensuring that the coverage area of ​​the heating coil is larger than the overall size of the electrode, so as to achieve a good heat transfer effect, and use the isolation layer to isolate the electrode layer and the heating layer to achieve overheating protection for the electrode layer, and the size of the isolation layer is 20 mm×20 mm; the preparation method of the CuO / Cu2O modified graphene flexible sweat glucose sensor is completed.

[0108] In step three of this embodiment, polyethylene terephathalate (PET) material with excellent stretchability, corrosion resistance and stability is used as a printing substrate, and microelectronic flexible printing technology is combined on the substrate to achieve the required electrode structure by stacking the printed materials layer by layer.

[0109] Preparation of the isolation layer:

[0110] 10g of white solid particles of polyvinyl alcohol and 5mL of anhydrous ethanol are dissolved in 100mL of aqueous solution, and heated in a water bath at 80°C. A magnetic stirrer is used at a speed of 500r / min to fully react. The water bath heating time is 5h. After the stirring and heating, a viscous liquid is formed as an isolation membrane source material. The viscous liquid is then placed in a microelectronic flexible printer and coated with a dispensing process to form a thin film with a thickness of 0.2 to 0.4mm. The film is allowed to stand for 24h and then transferred to an oven, dried at 80°C for 6h, to finally form a solidified isolation membrane, which is the isolation layer material.

[0111] The detection method of the CuO / Cu2O modified graphene flexible sweat glucose sensor:

[0112] Preparation of test solution

[0113] m. Weigh 0.09 g of glucose and 100 mL of deionized water, stir thoroughly to obtain a 5 mmol / L glucose solution, and then gradually dilute to obtain 0.1 mmol / L, 0.14 mmol / L, 0.18 mmol / L, and 0.2 mmol / L glucose test solutions;

[0114] n. Prepare artificial sweat according to the formula standard: sodium chloride 20g / L, ammonium chloride 17.5g / L, urea 5g / L, lactic acid 15g / L, acetic acid 2.5g / L;

[0115] o. Adjust the pH of the solution by adding buffer to prepare artificial sweat with different pH values;

[0116] Glucose detection

[0117] p. Conduct electrochemical test experiments at room temperature, connect the sensor chip to the experimental test platform chi600e electrochemical workstation, that is, connect the red chuck, green chuck, and white chuck of the workstation to the counter electrode, working electrode, and reference electrode respectively, connect the electrochemical workstation to the computer via USB, and use the supporting software of the test platform to set a series of system parameters to meet the initial test conditions of the glucose sensor;

[0118] After the initial parameters of the system were set, cyclic voltammetry was used to set different scan rates from 5mV / S to 150mV / S to test the CV curves of the CuO / Cu2O / RGO@Cu electrode during the redox reaction at different scan rates.

[0119] q. Using cyclic voltammetry (CV), under the same experimental environmental conditions such as ambient temperature and various parameters of cyclic voltammetry, the prepared 0.1 mol / L NaOH aqueous solution was first added to the electrode surface to observe the obtained CV graph. On this basis, glucose test solutions of different concentrations were added to the electrode surface respectively (after each addition of the test solution, the electrode surface was thoroughly cleaned and dried with deionized water to avoid errors in the next test of different concentrations), and the size of the generated current signal was observed to verify that the composite material improved the electrocatalytic activity. In order to obtain the best response to glucose, the current response of the prepared glucose sensor at different potentials was tested to screen out the appropriate applied potential of Ag / AgCl.

[0120] A large amount of interfering substances in the actual sweating process, such as ascorbic acid, uric acid, lactic acid, and glutamic acid, were added to the test samples. Through testing, it was determined whether the response current generated by the interfering substances would have a certain impact on the response current generated by glucose, and whether the deviation would affect the accuracy of the test results, so as to observe the selectivity of the prepared sensor.

[0121] Figure 1 This is a SEM picture of the CuO powder prepared in step 1 of Example 1. From the picture, it can be seen that the prepared CuO powder has a flaky structure with an average particle size of about 30 nm.

[0122] Figure 2The SEM picture of the Cu2O powder prepared in step 1 of Example 1 shows that irregular octahedral cuprous oxide crystals with an average particle size of 400-800 nm are obtained. It is found through experiments that more NaOH is added in the process of preparing Cu2O by glucose reduction method, the glucose concentration is low, and the water bath heating temperature reaches 70-80°C to prepare cuprous oxide with an octahedral structure. Crystals of this shape increase the specific surface area of ​​the material, so that the material performance is significantly improved. It can be seen that different molar ratios of reagent preparation schemes and heating temperatures will affect the shape and particle size of the cuprous oxide crystals formed.

[0123] Figure 3 This is a SEM picture of RGO prepared in step 2 of Example 1. It can be seen from the picture that the prepared reduced graphene oxide has a flaky structure composed of particles.

[0124] Figure 4 This is a SEM image of the CuO / Cu2O / RGO slurry material prepared in step five of Example 1. From the image, it can be observed that CuO is attached to the Cu2O and RGO substrates, and agglomeration occurs between the particles.

[0125] Figure 5 This is a schematic diagram of the structure of the electrochemical electrode prepared in step three of Example 1. The structure of the electrochemical electrode of the present invention is conducive to providing the maximum contact area between the sensitive modification material and the working electrode, thereby greatly enhancing the conductivity of the electrode and achieving better detection results.

[0126] Figure 6 This is a schematic diagram of the structure of preparing a micro heater in step 4 of Example 1.

[0127] Figure 7 This is a schematic diagram of the structure of the sensor prepared in Example 1;

[0128] Figure 8 This is a schematic diagram of preparing a sensor for detection in Example 1;

[0129] Fig. 9 The data analysis diagram of the sensor prepared in Example 1 using cyclic voltammetry to detect different concentrations of glucose, where 1 represents a glucose concentration of 0, 2 represents a glucose concentration of 0.1mmol / L, 3 represents a glucose concentration of 0.14mmol / L, 4 represents a glucose concentration of 0.18mmol / L, and 5 represents a glucose concentration of 0.20mmol / L; it can be seen from the figure that the potential range for glucose oxidation is between +0.1V and +0.5V, and there is a better current response when the potential is around +0.25V, so +0.25V is the optimal working potential of the electrode.

[0130] In order to test sweat interfering substances, after the selective permeable membrane is attached to the electrode, 10 μM sodium chloride, ascorbic acid, uric acid, fructose, lactose and sucrose are injected into the glucose solution to be tested for anti-interference testing. It is found that the addition of interfering substances has little effect on the change in the generated current. The results show that the prepared electrode has good stability. It can be seen that the flexible sweat glucose sensor based on CuO / Cu2O modified graphene oxide prepared in this embodiment has the basic ability to detect glucose in sweat, and has good stability, reproducibility and high sensitivity. Flexible electronic printing has green, low-cost, digital and personalized manufacturing characteristics, making the sweat glucose detection sensor more practical and cutting-edge.

Claims

1. A method for preparing a CuO / Cu2O modified graphene flexible sweat glucose sensor, characterized in that The method is specifically carried out in the following steps:

1. Preparation of CuO / Cu2O modified materials a. Mix CuCl2 powder with deionized water to prepare CuCl2 solution; Mix NaOH powder with deionized water to prepare NaOH solution; Add the NaOH solution to the CuCl2 solution while stirring, control the pH value of the solution to 7, and react fully to obtain a blue Cu(OH)2 suspension; b. Centrifuge the obtained Cu(OH)2 blue suspension in a low-speed centrifuge, wash with deionized water, repeat the centrifugation and washing process 3 to 4 times, wash once with anhydrous ethanol, remove the supernatant, and obtain a Cu(OH)2 blue colloidal precipitate; c. Place the obtained Cu(OH)2 blue colloidal precipitate in a quartz boat, control the temperature at 70-90°C to dry for 2h, then grind it into powder, transfer it to a vacuum drying oven, control the temperature at 200-250°C to roast for 3h, and use a ball mill to fully grind it to obtain fine black CuO powder; d. Mix CuSO4 and NaOH and react at room temperature to generate a blue Cu(OH)2 suspension. Heat in a water bath to 70°C, add glucose solution, and then add NaOH solution to react until the solution turns reddish brown. Keep the reaction at a constant temperature for 50 to 70 minutes and then stop heating. e. Filter the solution obtained in step d, rinse, dry, and then grind to obtain a dense reddish-brown Cu2O powder; 2. Preparation of reduced graphene oxide RGO f. Ultrasonic dispersion of the graphene solution to obtain a graphene dispersion, which is then dried in a cool place to obtain graphene oxide, and then the graphene oxide is placed in an agate mortar for full grinding to obtain a reddish-brown graphene oxide powder; g. dissolving the prepared red-brown graphene oxide powder in deionized water and dispersing by ultrasonication to obtain a red-brown uniform graphene oxide solution; h. The obtained reddish-brown uniform graphene oxide solution is transferred to a high-pressure reactor, and the temperature is controlled at 130-135° C. in a vacuum drying oven to perform a reduction reaction; i. The product obtained by the reduction reaction is repeatedly washed with deionized water for several times, and then repeatedly washed with anhydrous ethanol for several times; then filtered, impurities are removed, and dried. After sufficient grinding, fine reduced graphene oxide powder is obtained, which is recorded as RGO; 3. Preparation of electrochemical electrodes j. Electrochemical electrodes were prepared on PET film using a microelectronic flexible printing device based on a digital three-dimensional model; 4. Preparation of Microheater k. A heating device with a controlled temperature range of 32 to 40°C is used as a micro heater; 5. Cu x Coating of O / RGO composites 1. The CuO powder prepared in step c, the Cu2O powder prepared in step e and the RGO prepared in step i are placed in an agate mortar, pinene alcohol is added, and the mixture is fully ground to obtain a CuO / Cu2O / RGO slurry raw material. The CuO / Cu2O / RGO slurry raw material is coated on the effective contact area of ​​the working electrode in the electrochemical electrode prepared in step j, dried at room temperature, and then transferred to a vacuum drying oven and vacuum dried at 200-220° C. for 2-2.5 hours; then a Nafion perfluorinated solution is coated on the surface of the working electrode, the mass concentration of the Nafion perfluorinated solution is 5%, and the film is air-dried to obtain a CuO / Cu2O modified reduced graphene oxide electrode; 6. Sensor Assembly m. Assemble the flexible substrate, the microheater obtained in step k, the isolation layer and the CuO / Cu2O modified reduced graphene oxide electrode obtained in step l from bottom to top to complete the preparation of the CuO / Cu2O modified graphene flexible sweat glucose sensor.

2. The method for preparing a CuO / Cu2O modified graphene flexible sweat glucose sensor according to claim 1, characterized in that Step b controls the rotation speed of the low-speed centrifuge to 3500-4000 r / min.

3. The method for preparing a CuO / Cu2O modified graphene flexible sweat glucose sensor according to claim 1, characterized in that In step c, the vacuum degree of the vacuum drying oven is controlled to be -0.1 to 0.08 MPa.

4. The method for preparing a CuO / Cu2O modified graphene flexible sweat glucose sensor according to claim 1, characterized in that The molar ratio of CuSO4, glucose and NaOH in step d is 1:0.5:

3.

5. The method for preparing a CuO / Cu2O modified graphene flexible sweat glucose sensor according to claim 1, characterized in that In step g, the ultrasonic working power is controlled to be 130-195 W, and the ultrasound is turned on for 1.0 s and then turned off for 1.0 s, and the total time is 30 min.

6. The method for preparing a CuO / Cu2O modified graphene flexible sweat glucose sensor according to claim 1, characterized in that The electrochemical electrodes prepared in step j are a working electrode, a counter electrode and a reference electrode; the effective contact area of ​​the working electrode is circular, the counter electrode and the reference electrode are arc-shaped structures, and the counter electrode and the reference electrode form a surrounding structure around the effective contact area of ​​the working electrode.

7. The method for preparing a CuO / Cu2O modified graphene flexible sweat glucose sensor according to claim 1, characterized in that In step 1, the ratio of the amount of CuO, Cu2O and RGO substances is 1:1:0.

5.

8. The method for preparing a CuO / Cu2O modified graphene flexible sweat glucose sensor according to claim 1, characterized in that The preparation of the isolation layer in step m is as follows: 10g of white solid particles of polyvinyl alcohol and 5mL of anhydrous ethanol are dissolved in 100mL of aqueous solution, and heated in a water bath at 80°C. A magnetic stirrer is used at a speed of 100-500r / min to allow it to react fully. The water bath heating time is 3-5h. After the stirring and heating, a viscous liquid is formed as an isolation membrane source material. The viscous liquid is then placed in a microelectronic flexible printer and coated with a dispensing process to form a thin film with a thickness of 0.2-0.4mm. The film is allowed to stand for 24h and then transferred to an oven, dried at 80°C for 5-6h, to finally form a solidified isolation membrane.

9. The method for preparing a CuO / Cu2O modified graphene flexible sweat glucose sensor according to claim 1, characterized in that The method for detecting sweat glucose by the sensor is as follows: The sensor is connected to an electrochemical workstation, and the liquid to be tested is dropped into the effective contact area of ​​the working electrode of the sensor. The temperature of the micro heater is controlled to be 32-40° C. for detection and analysis.

Citation Information

Patent Citations

  • MEMS chip for measuring liquid viscosity and measurement method thereof

    CN108328563A

  • Biosensor with flexibility and elasticity and application thereof

    CN110865101A